Oral supplementation of specific collagen peptides combined with calf-strengthening exercises enhances function and reduces pain in achilles tendinopathy patients - Praet, S. F.; Purdam, C. R.; Welvaert, M.; Vlahovich, N.; Lovell, G.; Burke, L. M.; Gaida, J. E.; Manzanero, S.; Hughes, D.; Waddington, G. (Nutrients, 2019)
The current pilot study investigates whether oral supplementation of specific collagen peptides improves symptoms and tendon vascularisation in patients with chronic mid-portion Achilles tendinopathy in combination with structured exercise. Participants were given a placebo or specific collagen peptides (TENDOFORTE®) in combination with a bi-daily calf-strengthening program for 6 months. Group AB received specific collagen peptides for the first 3 months before crossing over to placebo. Group BA received placebo first before crossing over to specific collagen peptides. At baseline (T1), 3 (T2) and 6 (T3) months, Victorian Institute of Sports Assessment-Achilles (VISA-A) questionnaires and microvascularity measurements through contrast-enhanced ultrasound were obtained in 20 patients. Linear mixed modeling statistics showed that after 3 months, VISA-A increased significantly for group AB with 12.6 (9.7; 15.5), while in group BA VISA-A increased only by 5.3 (2.3; 8.3) points. After crossing over group AB and BA showed subsequently a significant increase in VISA-A of, respectively, 5.9 (2.8; 9.0) and 17.7 (14.6; 20.7). No adverse advents were reported. Microvascularity decreased in both groups to a similar extent and was moderately associated with VISA-A (Rc2:0.68). We conclude that oral supplementation of specific collagen peptides may accelerate the clinical benefits of a well-structured calf-strengthening and return-to-running program in Achilles tendinopathy patients.